2011
DOI: 10.4103/1319-3767.74483
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic measurement of abdominal esophageal length as a diagnostic tool in gastroesophageal reflux disease in infants

Abstract: Background/Aim:This study was conducted to provide sonographic measurements of the abdominal esophagus length in neonates and infants with and without gastroesophageal reflux disease (GERD) and to investigate its diagnostic value. GERD severity was also evaluated and correlated with esophageal length. It is a prospective case-control study.Materials and Methods:This prospective case-control study comprised 235 neonates and infants (120 without reflux and 115 with reflux). There were 40 children without reflux … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Videos were recorded right after water-drinking for at least 5 min. Frozen photos and SWE images were also saved after 5-min recording [ 23 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Videos were recorded right after water-drinking for at least 5 min. Frozen photos and SWE images were also saved after 5-min recording [ 23 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…There have been a number of studies which have looked at the role of ultrasound in the diagnosis of GOR and have concluded that it is the test of choice for symptomatic children. Various sonographic indicators of GOR have been proposed including measurement of the length of the abdominal oesophagus, 10–13 assessment of the oesophageal diameter, 14,15 assessment of the oesophageal wall thickness 10,16 and evaluation of the gastro‐oesophageal angle (His angle) 11 . While all these above mentioned measurements are important diagnostic indicators of GOR, we have found that the sonographic diagnosis can be more easily confirmed by real‐time (functional) assessment of the gastroesophageal junction and the visualisation of retrograde passage of gastric contents into the distal abdominal oesophagus 17 .…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%
“…[1] The study found that neonates and infants with reflux had a significantly shorter abdominal esophagus than subjects without reflux.However, this study has several critical methodological flaws that I would like to summarize in the following points:…”
mentioning
confidence: 99%
“…I have read with great interest the article by Dehdashti et al utilizing the sonographic measurement of abdominal esophageal length as a tool towards the diagnosis of gastroesophageal reflux disease (GERD) in infants and neonates. [ 1 ] The study found that neonates and infants with reflux had a significantly shorter abdominal esophagus than subjects without reflux.However, this study has several critical methodological flaws that I would like to summarize in the following points:…”
mentioning
confidence: 99%